2020
DOI: 10.3847/1538-4365/ab7377
|View full text |Cite
|
Sign up to set email alerts
|

YZiCS: Unveiling the Quenching History of Cluster Galaxies Using Phase-space Analysis

Abstract: We used the time since infall (TSI) of galaxies, obtained from the Yonsei Zoom-in Cluster Simulation, and the star formation rate (SFR) from the Sloan Digital Sky Survey (SDSS) Data Release 10 to study how quickly star formation of disk galaxies is quenched in cluster environments. We first confirm that both simulated and observed galaxies are consistently distributed in phase space. We then hypothesize that the TSI and SFR are causally connected; thus, both the TSI and SFR of galaxies at each position of phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
63
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 138 publications
16
63
3
3
Order By: Relevance
“…Thus, studies focused on timing the quenching of star formation in satellites have been able to benefit, in the last two decades, from the large statistics provided by wide-area photometric and spectroscopic surveys such as the SDSS, inevitably detaching themselves from the approaches adopted in the detailed studies of the few clusters with cold gas information available. In these statistical studies, the goal is not to determine quenching timescales for individual galaxies (something generally challenging with just UV/optical broad-band integrated photometry anyway), but to statistically infer them by matching the predictions of cosmological models of structure formation with the average properties of satellite galaxies, such as their passive fraction, their specific SFR distribution, and/or their 3D position within the cluster (e.g., Balogh, Navarro, & Morris 2000;Wetzel et al 2013;Haines et al 2015;Oman & Hudson 2016;Rhee et al 2020;Oman et al 2020). The use of merger trees in a cosmological context is the key element that makes this technique orthogonal to the one applied to individual galaxies and described in previous sections.…”
Section: Star Formation Quenching Timescalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, studies focused on timing the quenching of star formation in satellites have been able to benefit, in the last two decades, from the large statistics provided by wide-area photometric and spectroscopic surveys such as the SDSS, inevitably detaching themselves from the approaches adopted in the detailed studies of the few clusters with cold gas information available. In these statistical studies, the goal is not to determine quenching timescales for individual galaxies (something generally challenging with just UV/optical broad-band integrated photometry anyway), but to statistically infer them by matching the predictions of cosmological models of structure formation with the average properties of satellite galaxies, such as their passive fraction, their specific SFR distribution, and/or their 3D position within the cluster (e.g., Balogh, Navarro, & Morris 2000;Wetzel et al 2013;Haines et al 2015;Oman & Hudson 2016;Rhee et al 2020;Oman et al 2020). The use of merger trees in a cosmological context is the key element that makes this technique orthogonal to the one applied to individual galaxies and described in previous sections.…”
Section: Star Formation Quenching Timescalesmentioning
confidence: 99%
“…Starting from the work presented by Wetzel et al (2013), the refinement in the techniques used for the statistical estimate of quenching timescales suggests that the main quenching phase does not start at the time of infall but is significantly delayed (e.g., ∼2-6 Gyr; Haines et al 2015;Oman & Hudson 2016;Rhee et al 2020;Oman et al 2020), as the star formation in satellites is not immediately affected by the environment after infall (indicated in light blue in Figure 12). After this delay phase, quenching proceeds extremely fast, with satellites becoming passive in one billion year or less (the exact value being again heavily model-dependent).…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…When a galaxy falls into a cluster, during the first 1.5 − 2.5 Gyrs, star-formation quenching is slow. Thereafter, when a galaxy reaches to dense regions of the cluster, quenching proceeds more rapidly (Maier et al 2019;Roberts et al 2019;Łokas 2020;Rhee et al 2020). Galaxies in poor groups in the low-global-density environment need more time to evolve from star-forming galaxies into quenched galaxies (Lietzen et al 2012).…”
Section: Galaxy Evolution In the Supercluster And In The Cocoonmentioning
confidence: 99%
“…Some satellite galaxies enter their host cluster more susceptible to quenching because the environment of a previous, lower mass host has caused a decline in their star formation. These satellites are said to be preprocessed (Balogh et al 1999;Poggianti et al 1999;De Lucia et al 2012;Wetzel et al 2013;Bahé et al 2013;Taranu et al 2014;Roberts & Parker 2017;Haines et al 2018;Smith et al 2019;Pallero et al 2019;Pasquali et al 2019;Rhee et al 2020). Several studies have found a high fraction (∼ 50-65%) of quiescent galaxies in the immediate surroundings of clusters, which may be attributable to preprocessing (Wetzel et al 2013;Bahé et al 2013;Taranu et al 2014;Haines et al 2018;Pallero et al 2019).…”
Section: Introductionmentioning
confidence: 99%